FOLLOW-UP IN EDUCATION OF RESPONSIBILITY IN SENIOR PRESCHOOL AND JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2022)
The author describes the issues of effective implementation of continuity in the education of responsibility for children in preschools and primary schools.
Keywords: 1